Largest Abdominal CSF Pseudocyst – An Uncommon Complication of VP Shunt - Lukhi, Hiteshkumar D; Singh, M; Chakravarthy, S; Perwez, N (Nepalese Journal of Radiology, 2013)
Abdominal cerebrospinal fluid (CSF) pseudocyst is an unusual and important complication in patients with ventriculoperitoneal (VP) shunt. A 36yrs old male referred to the Department of Radiology for USG abdomen with complaints of gradually increasing distension of abdomen and provisional diagnosis of Alcoholic liver disease. Successive radiological investigations lead to diagnosis of malfunctioning VP shunt, secondary to abdominal CSF pseudocyst formation. Due to lack of suspiciousness patient had developed a giant abdominal CSF pseudocyst, size of which has not been reported in any literature so far. Hence, initial suspicion with appropriate investigation and early treatment can prevent morbidity and mortality. Nepalese Journal of Radiology / Vol.3 / No.1 / Issue 4 / Jan-June, 2013 / 89-90 DOI: http://dx.doi.org/10.3126/njr.v3i1.8820